Analysis Of the Health Decision-Making System for Elderly Hajj Pilgrimages in A Tour & Travel Company in Bandung Using the Simple Additive Weighting (SAW) Algorithm - Abdul Rahman Salim; Rr Isni Anisah Puspowati H; Dheni Apriantsani Budiman; Resti Aulia Damayanti (Journal of Economics, Management, and Entrepreneurship, 2026)
In Indonesia, the proportion of senior pilgrims performing the Hajj is rising annually, and by 2024, it will account for almost 30% of the total quota. In this case, particular consideration must be given to pilgrims' health readiness prior to departure. Inaccuracies, delayed information, and subjective decision-making may result from the manual health evaluation process used by a Bandung tour and travel agency for pilgrims. The purpose of this study is to use the Simple Additive Weighting (SAW) algorithm to develop a web-based decision support system and examine the decision-making process for the health of senior Hajj pilgrims. Rapid Application Development (RAD) is used in the system development process. Physical fitness, blood pressure, and blood glucose levels are among the health parameters that are used. The system's ability to objectively determine pilgrims' eligibility, rank them, and recommend testing results based on health categories (Accompanied, Unaccompanied, Recommended) demonstrates its objectivity. This solution reduces assessment errors, speeds up the evaluation process, and improves data management effectiveness.